Spontaneous extrusion of migrated fish bone in the neck after 48 hours of ingestion (Bangladesh Journal of Medical Science, 2011)
Foreign body in the neck usually will present with acute symptom of odynophagia or dysphagia. Migration of these foreign bodies to the adjacent structures or to the external skin may occur as late complication especially if the initial workup missed to detect their presence. Mostly the migrated foreign bodies were the fish bone as it has sharp ends. Depending on the tract that it made, serious complications may occur. We present a case of migrating fish bone in the neck with spontaneous extrusion without any complication. The foreign body was ingested not more than 48 hours before the extrusion. Key words: Fish bone migratory; neck; spontaneous; extrusion. DOI: http://dx.doi.org/10.3329/bjms.v10i2.7809 Bangladesh Journal of Medical Science Vol.10 No.2 Apr’11 pp.129-132